Measuring Trends and Cycles in Industrial Production in Norway 1896-1948 - Jan Tore Klovland (Norges Bank, 2015)
This paper presents new indices for industrial production in Norway covering the years 1896-1948. Separate annual and monthly indices of gross output and labour productivity are computed for 45 manufacturing and mining industries, using annually updated weights based on value added at factor cost. The new industrial production index shows somewhat stronger growth of output in the years before WWI and, in particular, in the 1930s, than the existing index published by Statistics Norway. The new monthly data set also provides a basis for identifying a business cycle chronology for Norway in the first half of the twentieth century.
hdl:11250/2495806
Keywords: E32; N64; O47; 330; industrial production; business cycles; labour productivity